Maternal Weight Predicts Children's Psychosocial Development via Parenting Stress and Emotional Availability - Bergmann, Sarah; Schlesier-Michel, Andrea; Wendt, Verena; Grube, Matthias; Keitel-Korndörfer, Anja; Gausche, Ruth; von Klitzing, Kai; Klein, Annette M. (Frontiers in Psychology, 2016)
Introduction: Maternal obesity has been shown to be a risk factor for obesity in children and may also affect children’s psychosocial outcomes. It is not yet clear whether there are also psycho-emotional mechanisms explaining the effects of maternal weight on young children’s weight and psychosocial development. We aimed to evaluate whether maternal body mass index (BMI), mother-child emotional availability (EA) and maternal parenting stress are associated with children’s weight and psychosocial development (i.e. internalizing/externalizing symptoms and social competence) and whether these predictors interact with each other. Methods: This longitudinal study included 3 assessment points (approx. 11 months apart). The baseline sample consisted of N=194 mothers and their children aged 5 to 47 months (M=28.18, SD=8.44, 99 girls). At t1, we measured maternal weight and height to calculate maternal BMI. We videotaped mother-child interactions, coding them with the Emotional Availability Scales (4th edition). We assessed maternal parenting stress with the Parenting Stress Index (PSI) short form. At t1 to t3, we measured height and weight of children and calculated BMI-SDS scores. Children’s externalizing and internalizing problems (t1-t3) and social competence (t3, N=118) were assessed using questionnaires: Child Behavior Checklist (CBCL1, 5-5), Strength and Difficulties Questionnaire (SDQ: prosocial behavior) and a checklist for behavioral problems at preschool age (VBV 3-6: social-emotional competence). Results: By applying structural equation modeling (SEM) and a latent regression analysis, we found maternal BMI to predict higher BMI-SDS and a poorer psychosocial development (higher externalizing symptoms, lower social competence) in children. Higher parenting stress predicted higher levels of externalizing and internalizing symptoms and lower social competence. Better maternal EA was associated with higher social competence. We found parenting stress to serve as a mediator in the association between maternal weight and children’s psychosocial outcomes. Children of mothers with an elevated BMI were at greater risk of lower social competence only when their mothers showed low levels of maternal EA (moderation). Conclusion: Interventional studies are needed that investigate the causal pathways between parenting stress, mother-child interaction quality and child outcomes. These aspects might be targets to improve the psychosocial development of the offspring of overweight or obese mothers.